IRRI 65 Years and Beyond: Building on Legacy, Driving Innovation, Increasing Resilience - International Rice Research Institute (2025)
• Special Remarks from Dr. Yvonne Pinto, Director General of the International Rice Research Institute (IRRI), including the rich history of IRRI, accomplishments, challenges, and future for the global rice industry. • As IRRI marks its 65th anniversary this year, it remains deeply embedded in the Philippine landscape, with Dr. Pinto emphasizing the dual imperative of building upon past achievements, while urgently responding to the unprecedented demands of the present era. • The 2025 World Rice Conference, taking place in Phnom Penh, Cambodia, from 7–9 November, serves as a strategic platform for these critical discussions, bringing together key players from across the global rice value chain.